Dynamic Behavior of Islamic Banking Customer Loyalty in Jakarta - Rusdianto, Rusdianto; Jasin, Mochammad (IQTISHADIA, 2021)
The attractiveness of Islamic banking lies in the profit-sharing system, service delivery, satisfaction, and promotion, where these components are interrelated with customers, which can influence customers to continue to choose Islamic banking services. This study aims to analyze the effect of service quality on customer satisfaction of Islamic banks, analyze the effect of service quality on customer loyalty of Islamic banks, and analyze the effect of customer satisfaction on customer loyalty of Islamic banks. The sample used in this study took the respondents of Islamic bank customers in Jakarta and then processed using SEM-PLS. The results showed that service quality had a significant effect on customer satisfaction, service quality significantly influenced customer loyalty, and customer satisfaction significantly influenced customer loyalty. This study recommends that there is a need to make products or services that are more in line with customer needs, the need to increase Islamic bank outlets or Automated Teller Machines (ATMs) owned by Islamic banks in locations that are more accessible and close to residential and business areas, and the need to conduct activities with customers periodically.